2021
DOI: 10.3389/fmed.2021.688805
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Ocular Anterior and Posterior Segment Lengths Among a Cataract Surgical Population in Shanghai

Abstract: Purpose: To investigate the distributions of the ocular anterior and posterior segment lengths among a cataract surgical population in Shanghai.Design: Cross-sectional study.Methods: Ocular biometric parameters of 23,462 eyes of 23,462 cataract surgery candidates were reviewed. Axial length (AL), anterior chamber depth (ACD), and lens thickness (LT) were obtained using IOL Master. Anterior segment length (ASL = ACD + LT), posterior segment length (PSL = AL – ASL) and the ratio of ASL to PSL (ASL/PSL) were calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Normally, the eyeball grows globally and uniformly with AL increasing. However, as suggested by our previous finding, extreme elongation of the eyeball was mainly due to the extension of the posterior segment ( 22 ). Thus, in eyes with extreme myopia, the LD, as an anterior structure, was not further increased with the eyeball extension.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Normally, the eyeball grows globally and uniformly with AL increasing. However, as suggested by our previous finding, extreme elongation of the eyeball was mainly due to the extension of the posterior segment ( 22 ). Thus, in eyes with extreme myopia, the LD, as an anterior structure, was not further increased with the eyeball extension.…”
Section: Discussionsupporting
confidence: 61%
“…The positive correlations of WTW and ASL with LD was consistent with our previous finding that toric IOLs rotate more in eyes with larger WTW and longer ASL ( 23 ). One reasonable explanation could be that WTW serves as an indicator of the horizontal diameter of the eyeball, thus representing the horizontal size of the anterior segment to a certain extent ( 24 ), and ASL has been established to represent the sagittal dimension of the anterior segment ( 22 , 23 ). Based on the above findings, we should pay special attention to the selection of an appropriate IOL in the clinical management of patients with these characteristics to avoid postoperative IOL decentration, tilt and rotation.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings revealed that the distribution of the AL and the calculated ASL and PSL values align with previous studies conducted among East Asian populations. The mean ASL was 7.58 ± 0.39 mm and the mean PSL was 17.12 ± 2.64 mm in a cataractous population in Shanghai [3]. This consistency suggests that the myopic population in Northern China shares biometric characteristics with other East Asian cohorts.…”
Section: Discussionmentioning
confidence: 69%
“…This study underscores the importance of considering both the AL and PSL while comprehending the progression of myopia. In the field of cataracts, research by Qi et al revealed that a longer ASL and a shorter PSL were associated with older age and the male gender, and the PSL correlated positively with the AL across the study population, indicating the importance of the PSL in the biometric assessment of cataractous eyes [3]. In the work of Jian et al, it was found that eyes that are more keratoconic may have a shorter AL and PSL but a deeper ACD [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation